EFFECT OF CAR, LDR, ROA, ROA AND NIM TOWARD THE COMMERCIAL BANK IN INDONESIA - Muhammad Alazis (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The purpose of this study to determine the effect of CAR, LDR, ROA, and NIM either partially or simultaneously on ROA in a conventional commercial bank in Indonesia. The study used secondary data drawn from the Indonesian Banking Statistics published by the Financial Services Authority. The research sample of 60 monthly time series data began in December 2014 s / d November 2019. The analysis tool using multiple linear regression, t-test, F test and coefficient of determination. The study concluded: 1) CAR significant negative effect on ROA, 2) LDR significant negative effect on ROA; 3) BOPO significant negative effect on ROA, 4) NIM significant negative effect on ROA, 5) CAR, LDR, ROA, and NIM simultaneous and significant impact on ROA.